The key application of serum tumor markers in testicular cancer: a review and update - Banerjee, Kishore G.; A. Shamsul Azlan, Muhammad Haziq; Kalaiarasu, Logeswaran; Hasrol Nizam, Haifa S. (International Journal of Advances in Medicine, 2021)
Testicular neoplasm is the most common solid tumor in male. The recent advancement in the medical field has made it possible to become one of the most highly treatable neoplasms. Testicular neoplasm is mainly classified into two main groups: non-seminomatous germ cell tumor and seminomatous germ cell tumor. In this review article, we analyzed the current role of serum biomarkers in diagnosis, prognosis, staging, measurement of response to therapy and early detection of relapse of testicular neoplasm. The commonly used tumor markers are alpha-fetoprotein (AFP), beta-human chorionic gonadotrophins and lactate dehydrogenase. Apart from them, a new set of tumor biomarkers like placentallike alkaline phosphatase, gammaglutamyltranspeptidase, miRNA, mitochondrial DNA and serum trace elements are also proven to be potentially helpful in the management of testicular neoplasm. Progressive elevation of serum tumor markers often indicates the presence of testicular cancer and aids in histological classifications. According to an additional category, the rate of elevation of respective biomarkers is advantageous to appropriately stage testicular neoplasm (S) in the tumor nodes metastases (TNM) staging classification. Besides, it is found that higher elevation of serum tumor markers is associated with a poorer prognosis. Post-treatment assessment where there is a rate of reduction of serum tumour biomarkers suggests the effectiveness of initial management of testicular neoplasm.